Purple corn cob (Zea mays L.) powder at different percentages on performance, fatty acid, nutrients profile, and lipoperoxidation in eggs from laying hens - Nizama, Milagros Nikole Flores; Vela, Connie Gallardo; Arevalo, Oscar Reategui; Delgado, Jimny Yoel Nuñez; Rivadeneira, Virginia (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The study aimed to evaluate the effect of purple corn cob powder (PCCP) at different percentages on performance, egg quality, egg weight loss, fatty acid profile, total solids, bromatological analysis, and lipoperoxidation in eggs from laying hens. Materials and Methods: One hundred twenty-eight Hy-Line Brown hens (29–35 weeks old) were divided into four treatments (0%, 0.2%, 0.4%, and 0.6% PCCP), with eight replicates and four hens per replicate. Results: Treatments with 0.4% and 0.6% PCCP significantly increased (p < 0.05) feed conversion ratio, laying percentage, and egg mass weight. Similar improvements were observed for yolk weight and Haugh units. There were no differences (p > 0.05) in shell weight, albumen weight, shell thickness, and yolk color. Treatments with 0.4% and 0.6% PCCP increased (p < 0.05) unsaturated fatty acids and decreased saturated fatty acids and thiobarbituric acid reactive substance levels. Eggs stored for 28 days showed lower weight loss (p < 0.05) in treatments with 0.2% and 0.4% PCCP. Conclusion: PCCP inclusion in laying hens’ diets can enhance productive indices, egg quality (both external and internal), increased unsaturated fatty acids, and help preserve egg properties during storage in the egg yolk. J. Adv. Vet. Anim. Res., 12(3): 760–773, September 2025 http://doi.org/10.5455/javar.2025.l939